Energy Saving and Renewable Energy production at University of Kashan, Kashan, Iran - Monemzadeh, Majid; Talebi-Dastenaei2, Mahnaz (Universitas Diponegoro, 2021)
University of Kashan was founded in 1974 and is the oldest institution of higher education in Kashan. Kashan (33° 58' 59